The COVID-19 Pandemic Impact on the Remittances and Major Economic Factors of Nepal: A Retrospective Assessment - Phuyal, Ram Kumar; Bhattarai, Madhusudan; Acharya, Yadu Nath (Economic Journal of Development Issues, 2024)
The COVID-19 epidemic has had a significant impact on Nepal, primarily due to the closure of businesses in key migrant labor destinations such as the Gulf countries, Malaysia, and South Korea. Remittances account for 26% of Nepal's GDP, but they have dropped significantly since COVID-19. This study examines the impact of a negative shock to remittances on macroeconomic variables and makes policy recommendations. The analysis finds that a drop in remittances correlates with slower growth in consumption (2.5%) and foreign exchange reserves (17.7%) over a 20-year period, using both quantitative and qualitative data. The result shows that the Nepalese migrant crisis, exacerbated by the economic downturn in destination countries, has led to a substantial decline in remittance inflows, causing a 15.33% monthly decrease. This poses a threat to Nepal's economy, affecting consumption, GDP growth, and key macroeconomic variables. The results thus emphasize the importance of immediate relief and bolstering economic recovery initiatives by investigating potential outcomes of the pandemic's impact on key economic indicators.